KONFLIK PSIKOLOGIS TOKOH KAKEK GARIN DALAM CERPEN â€œROBOHNYA SURAU KAMI â€KARYA A. A. NAVIS DAN RELEVANSINYA DALAM DUNIA PENDIDIKAN - Biya Ebi Praheta (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
The literary is the result of creativity, initiative, and the human work close to the public. Most of the literary can be describe the life in the community, can take the form of fiction and reality. One type of literary in short stories. The short story as a story has builder elements one of which is a plot. One part from the plot is the conflict that makes a story more lively and give memorable to readers. Interestingly conflict there in the short story titled â€œRobohnya Surau Kamiâ€by AA Navis. Kakek Garinfigure in these stories suffered enormous psychological conflicts that he was not sure with what has been carried out during life. Kakek Garinvery religious, but ended his life by suicide. The thing that makes this short story is very interesting to read and has a lot of moral values that can be taken the lesson. The moral values such as the value of perseverance and faith in God and do not like to brag because it would be bad for everyone else.